Potential Activities of Freshwater Exo- and Endo-Acting Extracellular Peptidases in East Tennessee and the Pocono Mountains - Mullen, Lauren; , Malcolm X Shabazz High School Aquatic Biogeochemistry Team; Boerrigter, Kim; Ferriero, Nicholas; Rosalsky, Jeff; Barrett, Abigail van Buren; Murray, Patrick J.; Steen, Andrew D. (Frontiers in Microbiology, 2018)
Proteins constitute a particularly bioavailable subset of organic carbon and nitrogen in aquatic environments but must be hydrolyzed by extracellular enzymes prior to being metabolized by microorganisms. Activities of extracellular peptidases (protein-degrading enzymes) have frequently been assayed in freshwater systems, but such studies have been limited to substrates for a single enzyme (leucyl aminopeptidase) out of more than 300 biochemically-recognized peptidases. Here we report kinetic measurements of extracellular hydrolysis of five substrates in twenty-eight freshwater bodies in the Delaware Water Gap National Recreation Area in the Pocono Mountains (Pennsylvania, USA) and near Knoxville, Tennessee (USA), between 2013 and 2016. The assays putatively test for four aminopeptidases (arginyl aminopeptidase, glyclyl aminopeptidase, leucyl aminopeptidase and pyroglutamyl aminopeptidase), which cleave N-terminal amino acids from proteins, and trypsin, an endopeptidase, which cleaves proteins mid-chain. Aminopeptidase and the trypsin-like activity were observed in all water bodies, indicating that a diverse set of peptidases is typical in fresh water. However, ratios of peptidase activities were variable among sites: aminopeptidases dominated at some sites, trypsin-like activity at others. At a given site the ratios remained fairly consistent over time, indicating that they are driven by ecological factors. Studies in which only leucyl aminopeptidase activity is measured may underestimate the total peptidolytic capacity of an environment, due to the variable contribution of endopeptidases.